The Olimpiada Popular: Barcelona 1936, Sport and Politics in an Age of War, Dictatorship and Revolution. Issue 1 (2nd January 2017) - Physick, Ray
ABSTRACT: In an attempt to undermine the IOC Games of 1936, organisations linked to the international worker sport movement responded to an invitation from the Comité Organizador de la Olimpiada Popular (COOP) to take part in an alternative Olympics, the Olimpiada Popular, in Barcelona in July 1936. It is estimated that some 10, 000 athletes and 25, 000 visitors were in Barcelona to celebrate the Olimpiada . Following the Fascist rising, which began in Spanish Morocco on 17 July, and reached mainland Spain the following day, the games had to be abandoned, despite attempts by the organisers to go ahead with a truncated programme. This article will assess the importance of the Olimpiada Popular in the context of the worker sport movement during the inter-war years and its significance with regard to the international campaign to boycott the Berlin Olympics.